A computational approach to validate novel drug targets of gentianine from Swertiya chirayita in Plasmodium falciparum. (October 2020) - Mahapatra, Rajani Kanta; Das, Mahin
Abstract: Gentianine is one of the compounds found in the plant Swertiya chirayita that is known for its antimalarial activity. However, its exact molecular mechanism of action is yet to be understood. In our present study, we applied several computational approaches to filter out and determine possible targets of gentianine in Plasmodium falciparum 3D7. Protein-protein networks formed the basis of one of our strategies along with orthologous protein analysis to establish essentiality. Out of 6 essential proteins from unique pathways, haloacid dehalogenase like-hydrolase ( Pf HAD1), phosphoenolpyruvate carboxykinase ( Pf PEPCK) and fumarate hydratase ( Pf FH) were screened as drug targets through this approach. Through our other strategy we established the predicted IC50 (PIC50) value of gentianine with a set of molecular descriptors from 123 Pathogen Box anti-malarial compounds. Afterwards through 2D structural similarity, L-lactate dehydrogenase ( Pf LDH) was established as another possible target. In our work, we performed in silico docking and analysed the binding of gentianine to the proteins. All of the proteins were reported with favourable binding results and were considered for complex molecular dynamics simulation approach. Our research clears up the molecular mechanism of antimalarial activity of gentianine to some extent paving way for experimental validation of the same in future. Highlights: A structure based screening approach has been applied to identify possible targets of gentianine. The targets of gentianine was established through 2D similarity search and PIC50 values. Molecular modeling and simlaton study was perormed to understand the binding conformations of gentianine.